PENANGGULANGAN TERHADAP TINDAK PIDANA PENCURIAN DENGAN PEMBERATAN (CURAT) YANG DILAKUKAN OLEH BEGAL DI WILAYAH HUKUM POLRESTABES SEMARANG - Andre Iswan Jatmiko; Rochmani Rochmani (Fakultas Hukum Universitas Stikubank, 2017)
Communities with lower levels of well-being tend to disregard the norms or rules of the applicable law. Seeing these conditions to meet the needs of a tendency to use all means so that these needs can be met. Of the ways used there is a violation and does not violate the norms hukum.Salah a form of crime that often occurs in the community is a criminal offense committed by a robber. Robber or in legal terms is theft with violence. The term phenomenon begal legislation criminal penalties stipulated in Article 365 CriminalCode. The problem according to the author in this study is how countermeasures against the crime of theft by weighting (nozzle) conducted by the robber in the jurisdiction Polrestabes Semarang and obstacles faced by the police in combating the criminal acts of theft by weighting (nozzle) conducted by begal in Semarang Polrestabes jurisdictions as well as efforts to overcome the problems. The method used in this research is sociological juridical is an approach that uses the principles and legal principles derived from the rules written, sociological is an approach that aims to clarify the real situation in society towards the issues examined in other words give meaning important on the steps of observation. The use of sociological juridical methods conducted by the researchers is not only based on laws and legal provisions relating to countermeasures against acts pidanapencurian by weighting (nozzle) conducted by the robber in the area of ​​Law Polrestabes Semarang. The results showed that the prevention of the crime of theft by weighting (nozzle) conducted by the robber in the area of ​​Law Polrestabes Semarang, namely by attempts non penal or preventive such as by making banners that contain extension or an appeal to the people to always remember safety self-owned assets, and outreach to the community. Efforts penal or repressive efforts undertaken by performing operations that continuously patrol Eagle Team Anti robber, Razia vehicle at night, arrest the perpetrators, and take action-action firmly against the perpetrators under criminal law. The obstacles faced by the police in response to acts of pidanapencurian by weighting (nozzle) conducted by the robber in the area of ​​Law Polrestabes Semarang. Barriers that are internal police investigators is the lack of personnel, so that the number of police investigators are not proportional to the number of population in a large area. Furthermore, the operational funds are extremely limited. Barriers that are external, namely a less litigious society, people with low education, people are less concerned with environmental safety.